HEALING OUR BROKEN ENVIRONMENT: Reflections on Eco-Faith Concerns of the Church after the 3.11-Japan’s Nuclear Disaster - Augustine, Sali (Asian Horizons, 2012)
It is one year after the Great Eastern Japan Earthquake on 11 March 2011 and the eventual accident in the Fukushima Daiichi Nuclear Plant occurred which contaminated the ocean and land by radiation, and tragically disrupted the daily life of an enormous number of people. Apart from the 19,100 people dead or missing1 in the event of earthquake-tsunami disaster, tens of thousands of people are evacuated from the neighbouring area of the nuclear plant, and numerous people are forced to live in fear and anxiety because of the nuclear disaster. The government, still not knowing exactly what to do with resettling, decontamination and reconstruction, has not made any sign of dropping the nuclear plants. Moreover around 3000 people are working daily inside the unsafe plant to repair, control and make it safe. There are 54 nuclear plants all over the country which has regular earthquake and tsunami warnings. People, who take an intellectual or scientific approach on environmental issues, discover the grave problems in the environment and the people who suffer them. Others, in the social field, begin from the suffering of the poor from environmental degradation and look to science for help. Some see human reality in explicitly ecological terms; for others, ecology is a spiritual vision or a theological world-view; and still others take an economic or political viewpoint, an ethical or theological one, in their approach to environmental issues. Still others gaze on the horizon and are simply puzzled by the topic or frankly disinterested in it. The issues of ecology therefore are multi-faceted, and a constant interplay amongst the viewpoints may be the best approach: intellectual-scientific aspects combining with the spiritualtheological dimensions for the sake of effective action and networking. Scientific controversy and socio-political-cultural complexities ought not to block people from prioritizing ecological issues and acting on them.